Screening approaches to cardiac amyloidosis in different clinical settings: Current practice and future perspectives - Caponetti, Angelo Giuseppe; Accietto, Antonella; Saturi, Giulia; Ponziani, Alberto; Sguazzotti, Maurizio; Massa, Paolo; Giovannetti, Alessandro; Ditaranto, Raffaello; Parisi, Vanda; Leone, Ornella; Guaraldi, Pietro; Cortelli, Pietro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Cardiac amyloidosis is a serious and progressive infiltrative disease caused by the deposition of amyloid fibrils in the heart. In the last years, a significant increase in the diagnosis rate has been observed owing to a greater awareness of its broad clinical presentation. Cardiac amyloidosis is frequently associated to specific clinical and instrumental features, so called “red flags”, and it appears to occur more commonly in particular clinical settings such as multidistrict orthopedic conditions, aortic valve stenosis, heart failure with preserved or mildly reduced ejection fraction, arrhythmias, plasma cell disorders. Multimodality approach and new developed techniques such PET fluorine tracers or artificial intelligence may contribute to strike up extensive screening programs for an early recognition of the disease.